(Poly)phenols and nitrolipids: Relevant participants in nitric oxide metabolism. (February 2023) - Fraga, César G.; Trostchansky, Andrés; Rocha, Barbara S.; Laranjinha, João; Rubbo, Homero; Galleano, Monica
Abstract: Nitric oxide ( NO) is an essential molecule able to control and regulate many biological functions. Additionally, NO bears a potential toxicity or damaging effects under conditions of uncontrolled production, and because of its participation in redox-sensitive pathways and oxidizing reactions. Several plant (poly)phenols present in the diet are able to regulate the enzymes producing NO (NOSs). In addition, (poly)phenols are implicated in defining NO bioavailability, especially by regulating NADPH oxidases (NOXs), and the subsequent generation of superoxide and NO depletion. Nitrolipids are compounds that are present in animal tissues because of dietary consumption, e.g. of olive oil, and/or as result of endogenous production. This endogenous production of nitrolipids is dependent on the nitrate/nitrite presence in the diet. Select nitrolipids, e.g. the nitroalkenes, are able to exert NO-like signaling actions, and act as NO reservoirs, becoming relevant for systemic NO bioavailability. Furthermore, the presence of (poly)phenols in the stomach reduces dietary nitrite to NO favoring nitrolipids formation. In this review we focus on the capacity of molecules representing these two groups of bioactives, i.e. (poly)phenols and nitrolipids, as relevant participants in NO metabolism and bioavailability. This participation acquires especial relevance when human homeostasis is lost, for example under inflammatory conditions, in which the protective actions of (poly)phenols and/or nitrolipids have been associated with local and systemic NO bioavailability.